Interstitial lung disease: course report - Kreuter, Michael; Poberezhets, Vitalii (Breathe, 2020)
According to the most recent update of the global burden of disease study [1], a rising number of years of lives lost and deaths due to interstitial lung diseases (ILDs) is to be expected in the coming years. This highlights the need for better tools to defeat these diseases worldwide. Nelson Mandela stated that “Education is the most powerful weapon which you can use to change the world.” The European Respiratory Society (ERS) realised over 5 years ago that there was a requirement to improve education in the field of rare lung disease, especially in ILDs.
Gesehen am 11.11.2025